Effect of targeted coagulopathy management and 5% albumin as volume replacement therapy during lung transplantation on allograft function: a secondary analysis of a randomized clinical trial - Vajter, Jaromir; Vachtenheim, Jiri; Prikrylova, Zuzana; Berousek, Jan; Vymazal, Tomas; Lischke, Robert; Martin, Archer Kilbourne; Durila, Miroslav (BMC pulmonary medicine, 2023)
BACKGROUND: Primary graft dysfunction (PGD) after lung transplantation (LuTx) contributes substantially to early postoperative morbidity. Both intraoperative transfusion of a large amount of blood products during the surgery and ischemia-reperfusion injury after allograft implantation play an important role in subsequent PGD development. METHODS: We have previously reported a randomized clinical trial of 67 patients where point of care (POC) targeted coagulopathy management and intraoperative administration of 5% albumin led to significant reduction of blood loss and blood product consumption during the lung transplantation surgery. A secondary analysis of the randomized clinical trial evaluating the effect of targeted coagulopathy management and intraoperative administration of 5% albumin on early lung allograft function after LuTx and 1-year survival was performed. RESULTS: Compared to the patients in the control (non-POC) group, those in study (POC) group showed significantly superior graft function, represented by the Horowitz index (at 72 h after transplantation 402.87 vs 308.03 with p < 0.001, difference between means: 94.84, 95% CI: 60.18-129.51). Furthermore, the maximum doses of norepinephrine administered during first 24 h were significantly lower in the POC group (0.193 vs 0.379 with p < 0.001, difference between the means: 0.186, 95% CI: 0.105-0.267). After dichotomization of PGD (0-1 vs 2-3), significant difference between the non-POC and POC group occurred only at time point 72, when PGD grade 2-3 developed in 25% (n = 9) and 3.2% (n = 1), respectively (p = 0.003). The difference in 1-year survival was not statistically significant (10 patients died in non-POC group vs. 4 patients died in POC group; p = 0.17). CONCLUSIONS: Utilization of a POC targeted coagulopathy management combined with Albumin 5% as primary resuscitative fluid may improve early lung allograft function, provide better circulatory stability during the early post-operative period, and have potential to decrease the incidence of PGD without negative effect on 1-year survival. TRIAL REGISTRATION: This clinical trial was registered at ClinicalTrials.gov (NCT03598907).
Keywords: primární dysfunkce štěpu; alografty; Hemorrhage; lidé; Reperfusion Injury; Primary Graft Dysfunction; krvácení; reperfuzní poškození; Lung Transplantation; Humans; transplantace plic; Allografts